(untitled) (Biodiversitas Journal of Biological Diversity, 2011)
Roesma DI, Santoso P. 2011. Morphological divergences among three sympatric populations of Silver Sharkminnow (Cyprinidae: Osteochilus hasseltii C.V.) in West Sumatra. Biodiversitas 12: 141-145. Silver sharkminnow (Osteochilus hasseltii C.V.) named by local people as Asang is one of potential Cyprinid fishes species found in several different ecosystems in West Sumatra. The differences of habitat types and another ecological factor among populations may have significant influences on variation and differentiation of morphological characters of this species. In order to elucidate the pattern of morphological divergence, meristic and morphometric characters of O. hasseltii in Singkarak and Dibawah Lake and adjoining river were compared. Phenogram based on cluster analysis showed specific morphological divergence among populations. There were 23 characters significantly different among all compared populations, the highest degree of differentiation was found between Singkarak and Dibawah Lake population (22 characters significantly different) and the most similar population were Singkarak Lake and Ombilin an outlet river of lake (only six characters significantly different).